Manajemen Laktasi Ibu Rumah Tangga Pada Pemberian ASI Eksklusif Di Wilayah Kerja Puskesmas Sumbersari Kabupaten Jember - Febriana Widyasari Dewi; FX. Ady Soesetijo; Farida Wahyu Ningtyias (Pascasarjana Universitas Jember, 2020)
The development of infant is affected by several factors, particularly providing exclusive breast feeding by the maternal, in which the exclusive breastfeeding contains complete nutrients that is needed by infant. However, the low rate of providing exclusive breast feeding in community may remain a challenge. A good lactation management takes important role in successful rate of exclusive breastfeeding. The lactation management can be defined as a either management or procedure performed by mothers during pregnancy, childbirth, and breastfeeding phase in order to facilitate breastfeeding activity. The lactation management itself is expected to support providing exclusive breastfeeding at least six months, in which the lactation management is necessary for both career-mother and housewife. The objective of this study was to assess the lactation management among housewife during breastfeeding activity. This was descriptive study by using quantitative approach, where the study design is case control. The location of this study is in work area of Primary Health Care of Sumbersari, Jember. This study found that lactation management is essential factor that affects breastfeeding activity among housewife. Keyword: Exclusive Breast Feeding, Lactation Management, Housewife